MiR-4486 enhances cisplatin sensitivity of gastric cancer cells by restraining the JAK3/STAT3 signalling pathway. (31st January 2022) - Zhou, Caijin; Chen, Linxia; Chen, Rihong; Xu, Feipeng; Huang, Zhe; Huang, Renwei; Wang, Weiwei; Xu, Qingwen
Abstract: Along with the occurrence of cisplatin resistance, treatment on gastric cancer (GC) becomes difficult. Therefore, researches on new therapeutic methods to revert cisplatin resistance are becoming increasingly urgent. qRT-PCR was used to quantify the expression of miR-4486, JAK3 in SGC-7901 or SGC-7901/DDP cell lines. WB was utilized to analyze the expression of JAK3, STAT3 and p-STAT3 in SGC-7901/DDP cell lines. CCK-8 assay was used to determine the IC50 of cisplatin on both cell lines and cell viability of SGC-7901/DDP cell lines. The target relationship between miR-4486 and JAK3 was determined by luciferase assay. MiR-4486 expression on apoptosis of SGC-7901/DDP cell lines was determined by flow cytometry. qRT-PCR testified that miR-4486 decreased in SGC-7901/DDP cells, and the expression of miR-4486 mimic increased significantly compared with miR-4486 NC. By CCK-8 assay, the IC50 of cisplatin on both cell lines were 9 μg/mL and 81.3 μg/mL, and overexpression of miR-4486 decreased the viability of SGC-7901/DDP cells. Compared with DDP group, the expression of miR-4486 accelerated SGC-7901/DDP cells apoptosis. Dual-luciferase assay suggested that JAK3 was the target gene of miR-4486. qRT-PCR and WB proved that miR-4486/JAK3 axis inhibit the activation of JAK3/STAT3 pathway, and JAK3 overexpression can partly reverse this. As shown by CCK-8 and flow cytometry, miR-4486 overexpression decreased viability and stimulated apoptosis of SGC-7901/DDP cells. However, JAK3 overexpression can also partly revert this. miR-4486 overexpression could decrease viability and improve apoptosis of SGC-7901/DDP cells to revert its cisplatin-resistance, and the mechanism may be related to JAK3/STAT3 signalling pathway.